Studies on Acacia mangium in Kemasul Forest, Malaysia. I. Biomass and productivity - Lim, Meng Tsai (Cambridge University Press, 1988)
Malaysia is establishing large-scale plantations for reforestation and the production of wood for pulp and paper as well as for light construction. The main species used currently is the exotic legume Acacia mangium. The above-ground biomass, litter production and litter accumulation in a four-year-old stand m Peninsular Malaysia were studied. The mean diameter at breast height (dbh) was 12 cm. The mean annual increment (MAI) m dbh of individual trees ranged from 0.9 to 5.1 cm while MAI in height of sample trees ranged from 2.9 to 5.5 m. The total above-ground biomass of the stand was 90.4 t ha-1 consisting of 57.6 t stem, 14.1 t branch and 5.4 t leaf. Litter production averaged 10.23 t ha-1 yr1with leaf litter making up 87.4% of the totaL Leaf litter accumulation amounted to 6.64 t ha1and the turnover constant of leaf litter was estimated at 1.35. The high productivity is discussed in relation to the high turnover of foliage and the low turnover of litter.